Multilevel resistive switching nonvolatile memory based on MoS2 nanosheet-embedded graphene oxide. (1st August 2016) - Shin, Gwang Hyuk; Kim, Choong-Ki; Bang, Gyeong Sook; Kim, Jong Yun; Jang, Byung Chul; Koo, Beom Jun; Woo, Myung Hun; Choi, Yang-Kyu; Choi, Sung-Yool
Abstract: An increasing demand for nonvolatile memory has driven extensive research on resistive switching memory because it uses simple structures with high density, fast switching speed, and low power consumption. To improve the storage density, the application of multilevel cells is among the most promising solutions, including three-dimensional cross-point array architectures. Two-dimensional nanomaterials have several advantages as resistive switching media, including flexibility, low cost, and simple fabrication processes. However, few reports exist on multilevel nonvolatile memory and its switching mechanism. We herein present a multilevel resistive switching memory based on graphene oxide (GO) and MoS2 fabricated by a simple spin-coating process. Metallic 1T-MoS2 nanosheets, chemically exfoliated by Li intercalation, were successfully embedded between two GO layers as charge-trapping sites. The resulting stacks of GO/MoS2 /GO exhibited excellent nonvolatile memory performance with at least four resistance states, >10 2 endurance cycles, and >10 4 s retention time. Furthermore, the charge transport mechanism was systematically investigated through the analysis of low-frequency 1/ f noise in various resistance states, which could be modulated by the input voltage bias in the negative differential resistance region. Accordingly, we propose a strategy to achieve multilevel nonvolatile memory in which the stacked layers of two-dimensional nanosheets are utilized as resistive and charge-storage materials.